Integrating patient safety and risk management: The role of law and healthcare organisations - Jahn Kassim, Puteri Nemie; Abd. Manaf, Noor Hazilah (Global Business and Social Entrepreneurship Resources (GBSE), 2016)
In creating an environment that minimises patient harm as well as avoiding the unnecessary loss of lives, there is a need for the inculcation of a safety culture in healthcare institutions. Healthcare organisations need to foster a culture that encourages continuous improvement of patient safety system within their institutions. Patient Safety is an integral part of the practice of medicine as it aims to reduce ‘the risk of unnecessary harm associated with healthcare to an acceptable minimum’ (WHO, World Alliance for Patient Safety 2009). Risk management, on the other hand, develops processes that minimise risks of harm within the organisation by identifying and analysing ‘potential hazards to prevent accidents, injuries, and other adverse occurrences through a minimum cost or minimize financial liability’ (MeSH 2009). Patient safety has the ability to support risk management efforts through new ways of understanding how things go wrong and applying new models to the problems. In supporting this, law plays a crucial role by giving health care providers incentives for delivering optimal care by preventing the risk of damage and safeguarding the legal protection of patients as well as strengthening professional discipline. Designing a model that integrates patient safety and risk management objectives requires the support of legal solutions, responsible and vigilant healthcare organisations to ensure systemic improvements in the safety and quality of the healthcare system.